Media Technology Innovation in the Transformation of the Entertainment Industry - Aldrin Putra; Aldi Firnanda; Muhammad Al Fikri Gunawan; Supina Batubara (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The entertainment industry has experienced significant paradigmatic changes thanks to breakthroughs in media technology. Innovations in media technology have been a key driver in the transformation of the entertainment industry, changing the way entertainment content is produced, distributed and consumed. This paper aims to present a comprehensive picture of how media technology innovations have changed the landscape of the entertainment industry. The biggest change brought about by media technology innovation is its impact on content production. In the past, entertainment content production was limited by budgets and expensive physical infrastructure. However, with the development of technology such as CGI (Computer Generated Imagery), VR (Virtual Reality), and AR (Augmented Reality), these limitations have been erased. Now, content producers have access to tools and techniques that enable them to create more immersive and engaging experiences for audiences